30 days of night: dark days ebook Dark days. - Niles, Steve (30 Days of Night: Dark Days (2007)., 2012)
Picking up from the literal ashes of 30 Days of Night, 30 Days of Night: Dark Days follows Stella Olemaun's efforts to warn the world about the threat the vampires pose the vampires who overran Barrow, Alaska, killing her husband and most of the town. Author: Steve Niles. Illustrator: Ben Templesmith. © Steve Niles, Lorelei Bunjes, and Idea and Design Works, LLC.